2009
DOI: 10.1007/s11552-009-9227-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Cubital Tunnel Recurrence Rates

Abstract: Cubital tunnel syndrome is the second most common nerve entrapment in the upper extremity. There are no current publications concerning the recurrence rates after endoscopic cubital tunnel release. The purpose of this study is to evaluate the recurrence rate of endoscopic cubital tunnel release compared to published reports of recurrence following open cubital tunnel procedures. We reviewed 134 consecutive cases of endoscopic cubital tunnel release in 117 patients. There were 104 cases in 94 patients with grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
0
26
0
13
Order By: Relevance
“…The technique presented here was adapted from one used previously for cubital tunnel syndrome. The latter was introduced in 1995 by Tsai et al [1] and since this princeps (principle) publication, two types of surgical endoscopically assisted nerve decompression techniques have been used: Knives [9][10][11][12] and scissors [13][14][15][16][17][18] techniques. Despite the excellent results sometimes reported in the literature, endoscopically assisted knife techniques are in our opinion hazardous because of the discrepancy between the size of the instruments and that of the nerve, and the inherent resulting potential for intraoperative nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The technique presented here was adapted from one used previously for cubital tunnel syndrome. The latter was introduced in 1995 by Tsai et al [1] and since this princeps (principle) publication, two types of surgical endoscopically assisted nerve decompression techniques have been used: Knives [9][10][11][12] and scissors [13][14][15][16][17][18] techniques. Despite the excellent results sometimes reported in the literature, endoscopically assisted knife techniques are in our opinion hazardous because of the discrepancy between the size of the instruments and that of the nerve, and the inherent resulting potential for intraoperative nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Die Rezidivrate beträgt gemäß Cobb et al [6] zwischen 0,02 und 5,24 %. Somit ist sie nicht höher als die in der Literatur beschriebene Rezidivrate bei offenen Dekompressionsverfahren.…”
Section: Komplikationenunclassified
“…The technique offers a minimally invasive alternative to open surgical decompression. It has been suggested that the limited soft tissue dissection will result in shorter recovery time and less scarring [ 113 ]. Many variations exist, but most involve a small incision at the condylar groove [ 112 , 114 -117 ].…”
Section: Endoscopic Releasementioning
confidence: 99%
“…Cobb et al examined recurrence of symptoms following 134 consecutive cases of endoscopic cubital tunnel release [ 113 ]. The authors observed a recurrence rate between 0.02 and 5.24 %.…”
Section: Endoscopic Releasementioning
confidence: 99%